2009
DOI: 10.1111/j.1600-0501.2009.01824.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized‐controlled clinical trial to evaluate bone preservation using implants with different geometry placed into extraction sockets in the maxilla

Abstract: Implant placement into extraction sockets will result in significant bone reduction of the alveolar ridge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
236
7
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(279 citation statements)
references
References 19 publications
21
236
7
9
Order By: Relevance
“…It also improves the implant's primary stability, avoiding buccal wall engagement in the anterior Al-Sabbagh & Kutkut region, and reducing the need for jumping distance augmentation. [41][42][43] McAllister and associates 41 reported safe and effective application after using variable thread tapered implants. Although the difference was not significant, Sanz and colleagues 43 reported less vertical and horizontal space using tapered implants than of cylindrical implants after immediate implant placements.…”
Section: Submerged or Transmucosal Implant Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…It also improves the implant's primary stability, avoiding buccal wall engagement in the anterior Al-Sabbagh & Kutkut region, and reducing the need for jumping distance augmentation. [41][42][43] McAllister and associates 41 reported safe and effective application after using variable thread tapered implants. Although the difference was not significant, Sanz and colleagues 43 reported less vertical and horizontal space using tapered implants than of cylindrical implants after immediate implant placements.…”
Section: Submerged or Transmucosal Implant Placementmentioning
confidence: 99%
“…[41][42][43] McAllister and associates 41 reported safe and effective application after using variable thread tapered implants. Although the difference was not significant, Sanz and colleagues 43 reported less vertical and horizontal space using tapered implants than of cylindrical implants after immediate implant placements. However, Lang and colleagues 40 found in a clinical trial that both cylindrical and tapered implants have shown similar shortterm outcomes with regard to wound healing and primary stability.…”
Section: Submerged or Transmucosal Implant Placementmentioning
confidence: 99%
“…En la literatura consultada, las investigaciones clínicas excluyeron los pacientes con los siguientes factores de riesgo local: enfermedad periodontal, caries activa e inadecuado control de la higiene oral. Se desprende de la literatura que el resultado estético final no se ve influenciado por el diseño geométrico del implante (17,18) . En los tratamientos de alvéolos intactos, uno de los componentes que requiere atención es el tamaño del GAP (brecha horizontal que permanece entre las paredes óseas y la superficie del implante después de su inserción).…”
Section: Figunclassified
“…In the literature reviewed, clinical studies excluded patients with the following local risk factors: periodontal disease, active caries and inadequate oral hygiene. It is clear from the literature that the geometric design of the implant does not affect the final aesthetic result (17,18) . In the treatment of intact sockets, the size of the gap (horizontal gap that remains between the bone walls and the surface of the implant after placement) requires special attention.…”
Section: Figmentioning
confidence: 99%
“…Pour des raisons liées au patient, l'option en deux étapes est privilégiée, bien que, aussi bien cliniquement que radiographiquement, l'implant aurait pu être posé le jour de l'extraction [10].…”
Section: Stratégie Chirurgicaleunclassified